PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF SPINNER ROULETTE UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM - Putri Isnaini Hidayah; Nur Aisyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The use of instructional media helps students understand the material more easily and improves learning outcomes. Especially in Islamic Cultural History (SKI) lessons, which are often perceived as boring, interactive media is needed to boost students’ interest in learning. One such media is spinner roulette, an educational game designed to enhance interactivity and student comprehension. This research was conducted at MAN 1 and MAN 2 Probolinggo to describe the development process and the impact of the spinner roulette media on students’ learning interest and outcomes. The research used the Research and Development (R&D) method with the Lee and Owens model, consisting of five stages: analysis, design, development, implementation, and evaluation. The results showed that the spinner roulette media was appropriate for use and improved student learning outcomes by 11.1% (from 69.3% to 80.4%). Regression analysis indicated a significant effect of the media on learning interest (p = 0.000 < 0.05), concluding that spinner roulette is effective in increasing students’ interest and learning outcomes.